DNA Damage and Oxidative Status of Full Term Babies Delivered by Spontaneous Vaginal Delivery and Caesarean Section - Kazanasmaz, Halil; Abuhandan, Mahmut (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objectives: At this study, it is aimed to research DNA damage and oxidative stress in infants with born timely normal spontaneous vaginal delivery (NSVD) and elective caesarean. Study Design: Healthy term babies born with NSVD (n=36) and elective caesarean section (n = 36) were included in the study. Determination of DNA damage was studied in fresh heparinized blood by the Comet Assay (mononuclear cell alkaline electrophoresis) method. Total oxidant capacity and total antioxidant capacity values were measured by using Erel method (colorimetric) on study day by autoanalysers and oxidative stress index values were calculated. Results: Mean total oxidant capacity, oxidative stress index and DNA damage values were significantly higher in babies born with NSVD compared to those born with elective cesarean section (p <0.001, p<0.001, p<0.001, respectively). Serum total antioxidant capacity values were not statistically significant (p=0.127). Conclusion: In this study, oxidative stress and DNA damage values of babies born with NSVD were found to be higher than those born by elective cesarean section. This suggests that there may be a relationship between the mode of delivery and oxidative stress, and that increased oxidative stress may also lead to DNA damage.